O cangaço no sertão d’Os desvalidos - Menezes, Aldair Smith (2010)
The cangaço and the backland have been recurrent themes in the Brazilian literature. In each epoch in which they are used as raw material for the construction of literary or cinematic texts, these terms assume distinct meanings. As a consequence, it is possible to say that the discovery of new emanated meanings from these words in the novel Os desvalidos (1993), written by Francisco José Costa Dantas, makes a singular analysis of the contemporary social relations possible. This narrative brings from these significants new meanings about Virgulino Ferreira, the Lampião, and his group as well. It reveals the presence of the woman among the cangaceiros and shows the daily life of common people, like Coriolano, a narrator character, Felipe, Zerramo, Maria Melona and other people, in the northeastern of Brazil, during the end of the nineteenth century and the beginning of the Estado Novo, in the twentieth century. People from this region were immerged in an unfinished modernization process of a capitalist order which was coming. Their fears, desires and uneasiness are disclosed in their personal dramas. The construction of this literary approach, therefore, is in the intersection point between the art of make literature and the historical fiction; a point in which events and memories of an epoch disclose the emblematic dialog between the social context and the cultural imaginary. The plot of this novel is driven in the backland man in the cangaço of the Os desvalidos backland, taking as a starting point the theoretical and methodological approach guided by the cultural studies, in such a way that, associated with the Literature, Gender Studies, History and Psychoanalysis, it is possible to have deeper analysis regarding the socio-cultural context of this masterpiece, taking advantage of some categories as ambivalence and chronotope, by Mikhail Bakhtin, a man-narrative, by Todorov Tzvetan; homology, by Lucien Goldmann, and free association, by Sigmund Freud.